2005
DOI: 10.1089/clo.2005.7.279
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cloned Pigs by Nuclear Transfer of Preadipocytes Established from Adult Mature Adipocytes

Abstract: The aim of the present study was to determine whether porcine preadipocytes can be efficient donor cells for somatic cell nuclear transfer (SCNT) in pigs. Primary culture of porcine preadipocytes was established by de-differentiating mature fat cells taken from an adult pig. The cell cycle of the preadipocytes could be synchronized by serum starvation for 1 day, with a higher efficiency than control fetal fibroblasts. Incidence of premature chromosome condensation following nuclear transfer (NT) of preadipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Compared to adult-derived donor cells, FFs resulted in a lower blastocyst rate. Our results were in agreement with the observation of Tomii et al (2005), in which the blastocyst rate of AP-derived embryos was slightly higher than that of FF-derived embryos. However, it was reported by different laboratories that FFs were superior to adult-derived donor cells.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Compared to adult-derived donor cells, FFs resulted in a lower blastocyst rate. Our results were in agreement with the observation of Tomii et al (2005), in which the blastocyst rate of AP-derived embryos was slightly higher than that of FF-derived embryos. However, it was reported by different laboratories that FFs were superior to adult-derived donor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Most previous publications failed to investigate the in vivo development or data collected were insufficient for statistical calculations (Faast et al, 2006;Tomii et al, 2005;Uhm et al, 2000;Yin et al, 2002). Our results confirmed that the capacity of nucleus to be reprogrammed cannot be evaluated exclusively by in vitro development; in contrast, in vivo development may be a more important characteristic.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations